Assessing the Role of Surabaya City Government's Responsiveness Toward Public Acceptance of COVID-19 Mitigation Policies - Wiranti, Dyah Ayu; Ariawantara, Putu Aditya Ferdian (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
Public acceptance, involving community awareness and support, is crucial for successful policy implementation. Despite challenges faced during the performance of the COVID-19 mitigation policy in Surabaya, the city government has shown responsiveness in addressing the issue. This study investigates the influence of the Surabaya City Government's responsiveness on public acceptance of the COVID-19 mitigation policy. Employing the Policy Acceptance Model and government responsiveness theory, a quantitative survey was conducted with 400 purposively sampled respondents. Results indicate a significant positive effect, indicating that higher government responsiveness leads to greater public acceptance of the COVID-19 mitigation policy. These findings support existing theories and validate the importance of community support in policy implementation